Methyl 4-Pentafluorosulfanylphenyl Sulfoximines - Hendriks, Christine M. M.; Reball, Jens; Bolm, Carsten (Synlett, 2015)
A low-cost and high-yielding synthetic route towards methyl 4-pentafluorosulfanylphenyl sulfoximines from the corresponding sulfide has been developed. The intermediate N-cyano sulfoximine was converted into the corresponding N-(1H)-tetrazole, and the NH-sulfoximine was modified by N-arylation and N-alkylation reactions.
Keywords: building blocks; pentafluorosulfanyl group; sulfoximine; organofluorine compounds; sulfilimine